A comprehensive assessment of mechanical and environmental properties of waste basalt powder-modified high strength mortars exposed to high temperature - Serhat Çelikten; Bilal Baran (Next Materials)
Waste Basalt Powder (BT) is a stone cutting workshop waste. The BT was recycled in the high strength mortars by Portland cement (PC). High temperature performance of the mortars were determined up to 800 ºC by in terms of weight and strength losses. The global warming potential (GWP) and Primary Energy (PE) of the mortars were calculated by Life Cycle Assessment (LCA) for the mortars and their environmental impacts were evaluated. GWP and PE decreased up to 23.9 % and 22.4 % in BT-containing mortars compared to the control group, respectively. Lower CO2 emission and PE values were determined in all the BT-containing mortars compared to the control group. Mortars containing 15 % BT had 9.92 % higher compressive strength than the control group with 14.35 % and 13.44 % lower GWP and PE values, respectively. The optimum BT content is 15 % in terms of strength, high temperature resistance and environmental impact. As a result, it is possible to successfully recycle BT material in the production of high-strength mortar that is more resistant to high temperatures.